(untitled) (Proceedings of International Conference on Special Education, 2025)
As educational technologies propel us towards a more advanced future, the foundational principle of ’leave no one behind, a transformative promise sealed in the 2030 Agenda of Sustainable Development Goals, becomes imperative. The 2019 UNESCO Recommendation on Open Educational Resources (OER) from the 40th UNESCO General Assembly emphasizes the need for member states to ’encourage inclusive and equitable quality OER. This call includes leveraging open educational practices to ensure greater access to educational materials and resources. In this evolving landscape, the spotlight is on Inclusive Open Educational Resources (iOER), a topic that has gained significant traction, particularly with the implementation of a national-level policy statement by Malaysia for its higher learning institutions. iOER stands as a beacon of accessibility, designed to cater to learners with disabilities, irrespective of their specific needs or abilities. Moreover, for persons with visual impairments, iOER provides materials in assistive devices like screen readers, while also incorporating features such as adjustable font sizes and contrast levels which can affect different level of visual impairments. These features empower learners with visual impairments to navigate educational content with ease, fostering a more independent and inclusive learning environment. However, despite the immense potential benefits, there are challenges hindering the widespread adoption of iOER. Misconceptions and barriers, including a lack of awareness, understanding of its value, technical skills, and support from educational and policy makers, persist within the OER advocacy community. Additionally, issues related to cost, copyright, and quality pose further barriers to adoption. In response to these challenges, iOER-enabled environments are deliberately designed to be flexible and adaptive. This flexibility allows learners to tailor their educational experience according to their needs, sharing content in various formats and across multiple platforms. SEAMEO SEN, as the regional center for special educational needs, stands at the forefront of this commitment. Expressing its dedication to being a referral center for iOER among its eleven SEAMEO Member Countries and beyond, SEAMEO SEN plays a pivotal role in championing and facilitating the adoption of inclusive practices.